2009
DOI: 10.1016/j.cattod.2008.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Promotion effect in Pt–ZnO catalysts for selective hydrogenation of crotonaldehyde to crotyl alcohol: A structural investigation

Abstract: Pt-ZnO catalysts prepared from different precursors, H2PtCl6 and Pt(NH3)4(NO3)2, and reduced at increased temperatures are used to achieve high selectivity towards crotyl alcohol in hydrogenation of crotonaldehyde. The ex-chloride catalyst shows a higher activity and selectivity than the ex-nitrate one. Transmission electron microscopy, electron diffraction, high-resolution imaging, energy dispersive X-ray spectroscopy and element mapping are used to characterize the catalysts in order to correlate the microst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Colloidal Pt nanoparticles were prepared adapting the method of Jones et al [26], employing a H 2 PtCl 6 ·H 2 O precursor since residual chlorine has been found to have a promotional effect in the selective hydrogenation of ␣,␤-unsaturated aldehydes [27]. To a stirred 10 ml aliquot of ethylene glycol (Fisher >99%) at 120 • C, 50 l of 0.1 M aqueous sodium hydroxide solution was added to promote nucleation.…”
Section: Synthesismentioning
confidence: 99%
“…Colloidal Pt nanoparticles were prepared adapting the method of Jones et al [26], employing a H 2 PtCl 6 ·H 2 O precursor since residual chlorine has been found to have a promotional effect in the selective hydrogenation of ␣,␤-unsaturated aldehydes [27]. To a stirred 10 ml aliquot of ethylene glycol (Fisher >99%) at 120 • C, 50 l of 0.1 M aqueous sodium hydroxide solution was added to promote nucleation.…”
Section: Synthesismentioning
confidence: 99%
“…Moreover, from Figure 3c, we can clearly see that the small nanoparticles consist of dots with alternate bright and grey contrasts: the bright dots represent columns of Pt atoms, and the grey dots represent columns of Zn atoms along the incident electron beam direction. It has been reported that, during the H 2 reduction at temperatures >250˝C, Pt nanoparticles interact with the ZnO support and that PtZn nanoalloys form [27,29,30,33]. Therefore, it is reasonable to conjecture that, after high temperature reduction, PtZn alloy nanoparticles were formed in our catalysts.…”
Section: Resultsmentioning
confidence: 92%
“…The activity differences must have originated from the effects of the H2 reduction treatment at different temperatures. Considering that PtZn alloy can form during H2 reduction at temperatures higher than 250 °C [27,29,30,33], we propose that the presence of the PtZn alloy nanoparticles in the Pt/ZnO NW-H300 catalyst may have improved the WGS activity. Detailed examinations revealed that there were no detectable PtZn alloy nanoparticles in the Pt/ZnO NW-H200 catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…purification of exhaust gas) [1][2][3] or for moderate temperature liquid-phase reactions (e.g. synthesis of organic chemicals) [4][5][6] or others. 7,8 However, as supported noble metals are prone to aggregation and leaching during reactions, deactivation often occurs quickly, which obviously should be avoided considering the high costs of these catalysts.…”
mentioning
confidence: 99%